Total Electrosynthesis of N, N‐Dimethylformamide From CO2 and NO3− - Shuai Yan; Shuai Chen; Morgan McKee; Alexandre Terry; Ralf Weisbarth; Nikolay Kornienko (Advanced Science)
Abstract Electrochemical C−N coupling presents a promising strategy for converting abundant small molecules like CO2 and NO3− to produce low‐carbon‐intensity chemicals in a potentially more sustainable route. A prominent challenge is the limited product scope, particularly for organonitrogen chemicals featuring a variety of functional groups, alongside the limited understanding of plausible reaction mechanisms leading up to these products. In light of this, the total electrosynthesis method is reported for producing N, N‐dimethylformamide (DMF), a widespread solvent and commodity chemical, from NO3− and CO2. This method enabled a notable production rate of 1.24 mmol h−1 gcat−1 for DMF employing a hybrid Ag/Cu catalyst. Additionally, an impressive Faradaic efficiency (FE) of 28.6% is attained for DMF through oxidative coupling of dimethylamine using Ag/Cu catalyst. Through a distinctive retrosynthetic experimental analysis, the DMF synthesis pathway is systematically deconstructed, tracing its origins from dimethylamine to methylamine, and ultimately to CO2 and NO3−. The investigation revealed that the hydrogenation of coupled intermediates proves to be the limiting step, rather than the C−N coupling steps in the synthetic pathway. Finally, using a combination of in situ measurements and retrosynthetic analysis, the possible mechanism is elucidated underlying DMF synthesis and identified subsequent routes for system improvement.